Respuesta :

Answer:

(3y - 1)(2y - 5)

Step-by-step explanation:

Given

6y² - 17y + 5

Consider the factors of the product of the coefficient of the y² term and the constant term which sum to give the coefficient of the y- term.

product = 6 × 5 = 30 and sum = - 17

The factors are - 2 and - 15

Use these factors to split the y- term

6y² - 2y - 15y + 5 ( factor first/second and third/fourth terms )

= 2y(3y - 1) - 5(3y - 1) ← factor out (3y - 1) from each term

= (3y - 1)(2y - 5) ← in factored form

ACCESS MORE